PENEGAKAN HUKUM PERATURAN DAERAH KOTA DENPASAR NOMOR 27 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH (RTRW) KOTA DENPASAR - Ni Putu Sri Rahayu Mulya Ningsih; I Ketut Sudiarta; Kadek Sarna (Kertha Negara : Journal Ilmu Hukum, 2014)
On this period utilization and usage of spatial arrangement and areas inDenpasar City increasing and less controllable along with accelerated development.Therefore problems arise like green channel violations, permission letter to makebuilding (IMB) violations, Bali style violations, porch violations, river borderviolations, building border violations, and etc. Government, in this case Department ofSpatial and Housing of Denpasar City, have the duty to enforce local regulation ofDenpasar city so the violations can be reduced. What Obstacles that faced by thegovernment of Denpasar City to enforce the local regulation. With utilize empiricalresearch method, discovered the obstacles that government faced distinguished be twofactors, namely juridical factors and non-juridical factors. Juridical factors is lack ofcriminl sanctions set by the local regulation it self. Whereas, the non-juridical factorsassociated with law enforcement institutions, equipment and facilities, and society.